2019
DOI: 10.1080/23328940.2019.1574199
|View full text |Cite
|
Sign up to set email alerts
|

Use of the heat tolerance test to assess recovery from exertional heat stroke

Abstract: Exercise or work in hot environments increases susceptibility to exertional heat illnesses such as exertional heat stroke (EHS). EHS occurs when body heat gain exceeds body heat dissipation, resulting in rapid body heat storage and potentially life-threatening consequences. EHS poses a dangerous threat for athletes, agriculture workers, and military personnel, as they are often exposed to hot environmental conditions that restrict body heat loss or contribute to body heat gain. Currently, there is limited guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 65 publications
0
49
0
Order By: Relevance
“…However, in this review, only one study identified haematological biomarkers (leucocytosis, and anaemia). While the evidence in this review may be limited given the few number of articles investigating and reporting haematological biomarkers, evidence from the literature suggests that EHS results in SIRS which causes coagulopathies and DIC [ 4 ]. These biomarkers are useful in determining the severity of EHS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in this review, only one study identified haematological biomarkers (leucocytosis, and anaemia). While the evidence in this review may be limited given the few number of articles investigating and reporting haematological biomarkers, evidence from the literature suggests that EHS results in SIRS which causes coagulopathies and DIC [ 4 ]. These biomarkers are useful in determining the severity of EHS.…”
Section: Discussionmentioning
confidence: 99%
“…The underpinning physiological mechanism of EHS is currently unknown, but evidence suggests that vascular endothelial damage occurs in response to hyperthermia [ 4 ]. Direct thermal injury to tissues facilitates endotoxin leakage from the intestinal mucosa and the release of cytokines into systemic circulation, thus inducing a systemic inflammatory response syndrome (SIRS) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These health-complications include: heat intolerance [22], neurological impairment [23], chronic kidney disease [24] and cardiovascular disease [25]. The burden of EHS not only relates to the health of the patient, but can also result in reduced occupational effectiveness [26,27], significant medical/legal expenses [28,29], and in some instances high-profile media criticism [30,31] of concerned governance bodies (e.g. employer).…”
Section: Introductionmentioning
confidence: 99%
“…Excess heat exposures is not only an environmental threat but also an occupational hazard for a large worker population engaged in hard manual labor in tropical settings [3] exposed to heat stress and strain [4]. Workers in high-heat industries such as iron and steel, foundries, smelters, brick-firing and ceramic, glass and rubber, bakeries, commercial kitchens, and mining are already subjected to high heat exposures on a day-to-day basis and have high potential for heat-related illnesses like heat exhaustion, heat stroke, and death [5][6][7][8][9] which is likely to increase in the future climate change scenario [10,11].…”
Section: Introductionmentioning
confidence: 99%